Evaluación de los procesos de oxidación avanzada: fenton, Uv/H2O2 y foto-fenton para la degradación de clorpirifós en aguas residuales a nivel laboratorio en la universidad de Cartagena (2018)
The advanced oxidation processes are part of the viable wastewater treatments in the country, these allow the purification of these through the generation of hydroxyl radicals. In the present work the effectiveness of the advanced oxidation processes (Fenton, Foto-Fenton and UV / H2O2) in the reduction of organophosphorus pesticides (chlorpyrifos) in the discharges coming from the laboratories of the agrochemical research group of the university was evaluated. from Cartagena; for this, preliminary tests were conducted and the influential variables in the oxidation processes were determined. A factorial design 22 was applied, with which the effect of the process variables (concentration of Fe + 2 and concentration of H2O2) could be observed. The evaluation of the application of the advanced oxidation methods Fenton, Foto-Fenton and UV / H2O2 for the degradation of chlorpyrifos in wastewater at laboratory level, was carried out in acid medium for the formation of the radical HO •, and thus degrading the chlorpyrifos present in the wastewater. Experimentally, it was determined that the concentration of 2.5 ppm and 540 ppm of Fe + 2 and H2O2 respectively was the most adequate, reaching an efficiency of 96.53% reduction of chlorpyrifos in the residual water with the Foto-Fenton method. The technical specifications were made to implement this process on a pilot scale. For the disposal of discharges, reference was made to resolution 631 of 2015, a legal standard that establishes the parameters and maximum values of permitted chlorpyrifos that must be met by a discharge.